DAMPAK CRYPTOCURRENCY TERHADAP PEREKONOMIAN MASYARAKAT - Mulono Apriyanto; Widyawati; Ahamad Rifa’i (Bajang Institute, 2021)
The development of information technology will be related to all fields including finance. Cryptocurrency (Cryptocurrency) or often referred to as virtual currency / digital currency is the result of a development of financial technology (financial technology). Digital currencies began to be widely used as a means of payment on the internet. The purpose of this currency is to Provide convenience and security in payment. With blockchain technology in it, making transaction costs cheaper. However, the Government in this case Bank Indonesia prohibits transactions using digital / virtual money because it has a harmful impact on the Financial System, Monetary Stability and Payment System in Indonesia. This study explains the impact of Cryptocurrencies on the Indonesian economy and the government's attitude towards existing technologies inside. In terms of the technology offered, cryptocurrency is a development of financial technology that allows to change paper money into digital money in financial transactions in the future. It is hoped that the government can review the technology contained in cryptocurrencies more deeply so that the policies made later do not prohibit the technology contained in cryptocurrencies and provide knowledge to the public to better understand about cryptocurrencies